2020
DOI: 10.3390/microorganisms8091332
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Lytic Bacteriophage vB_EfaS_PHB08 Harboring Endolysin Lys08 against Enterococcus faecalis Biofilms

Abstract: Enterococcus faecalis is an opportunistic pathogen that causes illnesses ranging from urinary tract infections to sepsis in humans and animals. However, the overuse of antibiotics has increased rates of drug resistance among E. faecalis isolates. Bacteriophages and their derivatives have recently been identified as good candidates for the treatment of drug-resistant bacterial infections. Here, we isolated a virulent E. faecalis phage, PHB08, using the double-layer plate method. The bioactivity of the phage was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…The bacteriophage lysin breaks down the peptidoglycan layer constituting the bacterial cell wall. Lysin has several advantages over traditional antibacterial drugs: (1) it has a completely different mechanism of action to conventional antibiotics, (2) it is expected to be advantageous in terms of safety as it has a very high selectivity for bacteria [ 5 ], (3) lysin also acts on bacteria in the state of biofilm formation [ 6 ], and (4) it is expected to have a low probability of developing resistant bacteria due to its high rate of action [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bacteriophage lysin breaks down the peptidoglycan layer constituting the bacterial cell wall. Lysin has several advantages over traditional antibacterial drugs: (1) it has a completely different mechanism of action to conventional antibiotics, (2) it is expected to be advantageous in terms of safety as it has a very high selectivity for bacteria [ 5 ], (3) lysin also acts on bacteria in the state of biofilm formation [ 6 ], and (4) it is expected to have a low probability of developing resistant bacteria due to its high rate of action [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a MRSA strain SA14 as the indicator, we isolated a bacteriophage designated vB_Saus_PHB21 (thereafter referred as PHB21) from an epidermal sample collected from a Siberian tiger ( Panthera tigris altaica ) in Qingdao Zoo (Qingdao, China) through the conventional double-layer agar method, as described previously (13, 14). Phenotypically, PHB21 formed small round transparent plaques with a clear boundary in the double agar ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A human origin MRSA strain SA14 was used as the indicator for bacteriophage isolation. Bacteriophage was isolated and purified according to methods described previously (13, 14). Phage morphology was observed using a 100-kV transmission electron microscope (HITACHI H-7650, Tokyo, Japan) with the same protocol as described by Chen et al (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, this study also suggested phage and endolysin as possible biocontrol agents that could destroy the biofilm formation of E. faecalis . Additionally, high stability of phages in different environmental conditions can increase their use in UTI [ 71 ]. Another interesting study on two-species biofilms investigated the effectiveness of hydrogel silicone urinary catheter treated with phage cocktail in inhibition of biofilm formation by a mixture of P. mirabilis and P. aeruginosa in an in vitro model using artificial urine.…”
Section: Phages Inhibition For Other Uropathogenic Bacterial Biofilmmentioning
confidence: 99%